DISRUPTIVE INNOVATION IN EDUCATION: : A bibliometrics study on Moocs - Rodrigues, Glauco Oliveira; Adriana Johann, Denise; Morgental Falkembach, Marcos; Cassanta Antunes, Marcelo; Felipe Dias Lopes, Luis; Emilia Camargo, Maria; Lucia Salvador Bizotto, Beatriz (Pensamento & Realidade, 2024)
The aim of this study is to present the research scenario involving MOOCS, a new learning format that has the potential to become a disruptive innovation when compared to traditional teaching-learning models. Descriptive and quantitative work, bibliometric in nature, seeks to raise the characteristics of academic production. For that, a bibliometric search was carried out in the Web of Science database, in which 2,079 articles published in the period from 2011 to 2020 were investigated, in the respective database, including the characterization of production, methodological aspects and related themes. Initially, the total number of publications was identified, characterized by their thematic areas, types of documents, year of publication, authors, funding agencies and institutions, countries and languages. The research was carried out using Excel tools and VOSViewer software. It is also observed that the degree of cooperation between the authors is significant. Among those that stand out more are Kloos C.D. and Hoyos A.C. It can be seen that the main authors in the area are Spanish, despite the fact that this education model emerged in the United States in 2008.